Alcohol intoxication and sexual risk intentions: Exploring cultural factors among heavy drinking women. (August 2022) - Eakins, Danielle R.; Neilson, Elizabeth C.; Stappenbeck, Cynthia A.; Nguyen, Hong V.; Cue Davis, Kelly; George, William H.
Highlights: Women are at high risk for sexually transmitted infections. Risk and protective factors associated with sexual risk intentions were examined. Drinking and STI risk perception were associated with sexual risk intentions. Race and ethnic identity were associated with STI risk perception. Abstract: Introduction: Sexually Transmitted Infections (STI) rates are the highest of the last 20 years, with people of color and women particularly affected. Ongoing research has identified risk factors (e.g., alcohol intoxication) and protective factors (e.g., risk perception) for sexual risk behaviors, such as inconsistent condom use. Depending on behavioral norms within a group, ethnic identity (EI) – the exploration and sense of belonging to one's ethnicity – may be a risk or protective factor. This study examined the relations between EI, alcohol intoxication, and STI risk perception on sexual risk intentions among women of color (WOC) and white women (WW). Methods: Cisgender women ( N = 390; 35% WOC; 65% WW) completed measures and were randomly assigned to an alcohol condition (0.10% BrAC vs control). They projected themselves into an eroticized scenario and self-reported two aspects of STI risk perception (personal, partner) and two sexual risk behaviors (condomless sex intentions, condom decision abdication intentions). Results: Path analysis indicated that intoxicated women endorsed higher sexual risk intentions compared to women in the control group. Personal STI risk perception was negatively associated with sexual risk intentions. Indirect effects indicated that race was indirectly associated with both indicators of sexual risk, such that WOC reported higher perceived personal STI risk and subsequently endorsed lower sexual risk intentions compared to WW. Surprisingly, EI was associated with higher perceived partner risk for WW only. Conclusions: Prevention initiatives that address STI risk perception, condom assertion behaviors, and alcohol may be effective for mitigating women's sexual risk behaviors.